Synthesis, characterization, monolayer assembly and 2D lanthanide coordination of a linear terphenyl-di(propiolonitrile) linker on Ag(111) - Chen, Zhi; Klyatskaya, Svetlana; Urgel, José I.; Écija, David; Fuhr, Olaf; Auwärter, Willi; Barth, Johannes V.; Ruben, Mario (Beilstein Journal of Nanotechnology, 2015)
As a continuation of our work employing polyphenylene-dicarbonitrile molecules and in particular the terphenyl derivative 1 (TDCN), we have synthesized a novel ditopic terphenyl-4,4"-di(propiolonitrile) (2) linker for the self-assembly of organic monolayers and metal coordination at interfaces. The structure of the organic linker 2 was confirmed by single crystal X-ray diffraction analysis (XRD). On the densely packed Ag(111) surface, the terphenyl-4,4"-di(propiolonitrile) linkers self-assemble in a regular, molecular chevron arrangement exhibiting a Moiré pattern. After the exposure of the molecular monolayer to a beam of Gd atoms, the propiolonitrile groups get readily involved in metal–ligand coordination interactions. Distinct coordination motifs evolve with coordination numbers varying between three and six for the laterally-bound Gd centers. The linker molecules retain an overall flat adsorption geometry. However, only networks with restricted local order were obtained, in marked contrast to previously employed, simpler polyphenylene-dicarbonitrile 1 linkers.
Keywords: di(propiolonitrile) linker; lanthanides; metal–organic networks; molecular self-assembly; organic monolayers; single crystal X-ray diffraction analysis; UHV-STM